2010
DOI: 10.1152/ajpgi.00423.2009
|View full text |Cite
|
Sign up to set email alerts
|

Tauroursodeoxycholic acid reduces endoplasmic reticulum stress, trypsin activation, and acinar cell apoptosis while increasing secretion in rat pancreatic acini

Abstract: Malo A, Krüger B, Seyhun E, Schäfer C, Hoffmann RT, Göke B, Kubisch CH. Tauroursodeoxycholic acid reduces endoplasmic reticulum stress, trypsin activation, and acinar cell apoptosis while increasing secretion in rat pancreatic acini.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…On the other hand, in endocrine pancreatic cells TUDCA was a useful tool to reduce ER stress (31). We tested this bile salt derivate with ER chaperone-like characteristics in exocrine acinar cells, thereby reducing ER stress, trypsin activation, and apoptosis (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in endocrine pancreatic cells TUDCA was a useful tool to reduce ER stress (31). We tested this bile salt derivate with ER chaperone-like characteristics in exocrine acinar cells, thereby reducing ER stress, trypsin activation, and apoptosis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that tauroursodeoxycholic acid (TUDCA), a bile salt with ER chaperone-like properties, reduced hallmarks of acinar cell overstimulation and ER stress in isolated rat acinar cells in an in vitro system (35).…”
mentioning
confidence: 99%
“…Based on previous literature, and a previous experiment (data not shown), the present study selected to treat cells with 1 mmol/l TUDCA for 3 h in vitro to ensure cell survival (15). The present study demonstrated that glycerin content in the TUDCA+TNF-α group was reduced significantly, and that dispersal of lipid droplets in the TUDCA+TNF-α group was reduced, compared with the TNF-α group.…”
Section: Discussionmentioning
confidence: 58%
“…TUDCA, an endogenous bile acid known to attenuate ER stress, 39,40 blocked the TGF-β1-induced expression of GRP78/94 and ATF6 (Figure 7b). TUDCA also inhibited XBP-1 splicing induced by TM or TG.…”
Section: Tgf-β1 Induces Persistent Er Stress That Results In Emt and mentioning
confidence: 95%